Pola Hubungan Ketetanggaan di Masyarakat Urban: Studi Kasus di Kampung Osing, Jember (The Pattern of Neighbourhood Relation in Urban Society: Case Study in Kampung Osing, Jember) - Hayati, Antika; Yuswadi, Hary (e-Sospol, 2019)
AbstractThe city center is often regarded as a dense settlement structure and full of various interests. In Indonesia, thedensity of occupation also caused various types of migrants from the region to color the urban culture. in fact,various traditional cultures also affect the inhabitants of the city so tha t the term kampung town appears. Theprocess of agglomeration and urbanization that occurred in the city of Jember also affected villages in the citycenter, one of which was Osing Village which was a (melting pot). The characteristics of the residents who livein this village are mostly Javanese and Madurese, this ethnic difference can lead to an interaction betweenvillage residents in the form of adjustment, competition, and tension. The purpose of this study is to describe thepattern of neighboring rel ationships in urban communities. This study uses a descriptive qualitative approach.The results of the study show that the relationship pattern of neighboring communities living in Kampung Osingcan be identified by the joint activities they undertake. Th e characteristics of the people of Kampung Osing arediverse, and live in densely populated settlements. This makes them experience changes in social life. Suchchanges are like the emergence of social stratification formed by the existence of differences in socio economicstatus both high, medium and low which are influenced by wealth ownership, employment, and educationalattainment which ultimately affects the pattern of interactions that occur. On the other hand, the lack of spacemakes the occupying co mmunity experience the configuration of private space into public spaces and publicspaces into private spaces. The neighbor relationship pattern that occurs because of crowded housing andinconvenience makes people experience "dissatisfaction" caused by t he absence of standard regulations aroundthe local environment such as the absence of a prohibition on parking vehicles in a narrow alley. In addition,they also built several social networks that were influenced by, place factors, social status factors a nd thecommon area of origin.Keywords:n eighbourhood r elations , s pace c onfiguration, s ocial s tratification